Method for preparing battery-grade nickel sulfate through collaborative purification of crude nickel sulfate and crude nickel carbonate
By using a synergistic purification method of crude nickel sulfate and crude nickel carbonate, the problems of low impurity removal efficiency, high cost, and serious environmental pollution in existing nickel sulfate purification technologies have been solved. This method enables the production and recycling of high-purity battery-grade nickel sulfate, reducing energy consumption and environmental impact.
Patent Information
- Application Number
- CN202511586498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-01
- Publication Date
- 2026-01-06
AI Technical Summary
Existing nickel sulfate purification technologies suffer from problems such as insufficient impurity removal efficiency, low raw material utilization, difficulty in achieving battery-grade product purity, high environmental impact, and high energy consumption. In particular, the complexity and high toxicity of hexavalent chromium processing lead to high production costs, and the waste residue and waste liquid generated by traditional processes cause serious pollution.
A method for the synergistic purification of crude nickel sulfate and crude nickel carbonate is adopted. By optimizing the raw material ratio, introducing a synergistic neutralization strategy, multi-stage fine impurity removal and efficient concentration and crystallization technology, including steps such as alkaline washing, oxidation-reduction, precipitation, activated carbon adsorption and ion exchange, combined with precise pH and ORP control, to achieve efficient removal of impurities such as iron, chromium and aluminum, and reduce environmental pollution through resource recycling.
It significantly improves nickel recovery rate and product purity, reaching battery-grade standards, reduces production costs and energy consumption, realizes green production and resource recycling, and ensures high quality of lithium-ion battery cathode materials.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nickel salt production and purification, and discloses a method for preparing battery-grade nickel sulfate by co-purification of crude nickel sulfate and crude nickel carbonate. Background Technology
[0002] Nickel sulfate is the core nickel source for producing cathode materials for lithium-ion batteries, and its purity level directly determines the battery's performance, stability, and cycle life. With the rapid development of the global new energy vehicle and energy storage industries, the market demand for high-purity, ultra-low impurity battery-grade nickel sulfate has experienced explosive growth.
[0003] Currently, the main raw materials for the industrial production of nickel sulfate are diverse, including nickel sulfide concentrate, nickel matte, various nickel scraps, or crude nickel sulfate products. Traditional processes typically start from these raw materials and proceed through a series of steps such as acid leaching, multi-stage purification, concentration, and final crystallization. However, these unpurified nickel raw materials generally contain various impurity elements harmful to battery performance, such as iron, chromium, copper, aluminum, calcium, magnesium, and a range of organic compounds. Even trace amounts of these impurities can significantly affect the electrochemical performance of batteries. Therefore, removing these impurities from nickel sulfate products to extremely low levels, typically down to parts per million or even parts per billion, is a major technical challenge in the production of battery-grade nickel sulfate.
[0004] Existing nickel sulfate purification technologies generally suffer from several problems in practical applications. Firstly, regarding impurity removal efficiency, while traditional hydroxide precipitation methods can remove impurities such as iron and aluminum, they often require complex pH segmentation control and redox operations, limiting their ability to handle other impurities such as hexavalent chromium present in the solution. Hexavalent chromium, in particular, due to its high toxicity and difficulty in direct precipitation, usually requires a reduction reaction to convert it to trivalent chromium before precipitation removal, undoubtedly increasing process complexity and production costs. Secondly, regarding raw material utilization efficiency, existing processes tend to use crude nickel sulfate or crude nickel carbonate as the nickel source alone, potentially leading to high raw material procurement costs. Furthermore, the purification process requires the additional input of large amounts of acid or alkali to adjust the system pH, thus increasing reagent consumption and operating costs.
[0005] Furthermore, existing methods also face challenges in terms of product purity. Even after multi-stage precipitation and purification processes, trace amounts of metallic impurities and organic matter that are difficult to remove by conventional methods may still remain in the solution. Without further deep purification steps, such as activated carbon adsorption and ion exchange, the final nickel sulfate product will struggle to meet the stringent requirements for impurities such as iron, chromium, and copper in battery-grade applications. From an environmental perspective, traditional purification processes typically generate large amounts of waste residue and wastewater containing nickel and other heavy metals. Improper disposal of these wastes can cause serious environmental pollution. Therefore, effectively recycling wastewater and resource-based treatment of waste residue are crucial environmental issues that the industry must address. Finally, the multi-stage chemical reactions, frequent pH adjustments, and conventional evaporation, concentration, and crystallization processes often involve high energy consumption, posing a significant challenge in today's increasingly green production and cost-control environment.
[0006] In conclusion, the industry urgently needs to develop a novel synergistic purification method. This method should be able to efficiently utilize crude nickel raw materials, effectively simplify the process flow, significantly improve the removal efficiency of impurities, reduce overall energy consumption and environmental pollution, and ultimately stably produce ultra-high purity nickel sulfate products that fully meet battery-grade standards. Summary of the Invention
[0007] This invention addresses the problems of insufficient impurity removal efficiency, low raw material utilization, difficulty in achieving battery-grade purity, high environmental impact, and high energy consumption in existing crude nickel sulfate purification technologies. It provides a method for the co-purification of crude nickel sulfate and crude nickel carbonate to prepare battery-grade nickel sulfate. This invention aims to achieve clean and efficient production of high-purity battery-grade nickel sulfate by optimizing raw material ratios, introducing a synergistic neutralization strategy, employing multi-stage refined impurity removal, and utilizing efficient concentration and crystallization technology.
[0008] To achieve the objective of this invention, the technical solution adopted is as follows: a method for preparing battery-grade nickel sulfate through the synergistic purification of crude nickel sulfate and crude nickel carbonate, wherein the method comprises the following steps: S1 Weigh out crude nickel sulfate and nickel carbonate in a ratio of 1.5~2:1; crush the crude nickel carbonate to a particle size of 1~3 mm, sieve the crude nickel sulfate to 1~5 mm and remove obvious mud and sand; prepare process water and pass it through a 1~5 μm filter screen for later use. S2. Add process water to reactor 1, with the process water accounting for 30-40% of the reactor 1 volume; add crude nickel sulfate to reactor 1 all at once, and start the stirrer to stir at a speed of 60-80 rpm and a temperature of 60-70°C for 60-80 minutes; divide the crude nickel carbonate into 4-5 portions, and add one portion of crude nickel carbonate to the reactor every 20-30 minutes, while maintaining a speed of 60-80 rpm and a temperature of 60-70°C; add sodium carbonate to adjust the pH of the solution to 2.1-2.3, and maintain this pH for 20-30 minutes. CO2 and acid mist generated during S3 synergistic neutralization are discharged from the top of the reactor and enter the alkaline scrubbing tower. The alkaline scrubbing tower is filled with sodium hydroxide solution and the solution is kept circulating to ensure that the pH of the gas outlet is stable at 8-9. The gas after alkaline scrubbing is further purified by an activated carbon adsorber and finally meets the emission standards. S4. Start the diaphragm metering pump and pump the mother liquor in reactor 1 into reactor 2 at a constant flow rate of 10-20 L / min. Reactor 2 is equipped with a frame stirrer and a jacketed cooling system. The temperature inside the reactor is controlled at 60-65℃ and stirred at a speed of 40-60 rpm. Divide the 20-25% sodium hypochlorite solution into 4-5 equal portions using a peristaltic pump and add each portion to reactor 2 at intervals of 15-20 minutes. During the entire addition process, ensure that the ORP value eventually stabilizes at 340-350 mV and maintain this state for 10-20 minutes. Continue stirring for 30-60 minutes to ensure complete oxidation reaction. Then, pump in a 30-32% sodium carbonate solution at a rate of 10-20 L / h to adjust the pH to 3.1-3.3. After the pH reaches the set value, continue stirring and keep warm for 60-80 minutes to allow the generated Fe(III) hydroxide and Al(OH)3 precipitate to fully coagulate and form easily separable flocculent matter. S5 pumps the slurry in reactor 2 to a plate and frame filter press via a screw pump. The filtration pressure is set to 4-6 bar until the filter cake water content stabilizes at 60-75%. The filter cake is washed 1-3 times with warm water at 40-50°C, with each wash using 0.5-0.8 times the volume of the filter cake. The filtrate after washing is collected and sent to the upstream process water tank for reuse. The filter cake is automatically unloaded into a sealed hopper for use as a nickel-containing byproduct or for further recycling. S6 pumps the mother liquor after preliminary solid-liquid separation into reactor 3 via a diaphragm pump at a flow rate of 10-20 L / min. Reactor 3 is equipped with a paddle stirrer and a jacketed heating system, maintaining the temperature inside the reactor at 54-56℃ and stirring at 40-60 rpm. A 30-32% sodium sulfite solution is divided into 3-4 equal portions and added to reactor 3 at 20-30 minute intervals. Stirring is maintained during the addition process, and the temperature is kept at 54-56℃. After the reducing agent is added, stirring continues and the temperature is maintained for 45-60 minutes to ensure that Cr(VI) is completely reduced to Cr(III), and the Cr(VI) concentration in the solution is below 0.1 mg / L. A 30-32% sodium carbonate solution is pumped into reactor 3 to adjust the pH of the system to 5.0-5.1. After the pH reaches the set value, stirring continues and the temperature is maintained for 80-90 minutes to promote the full precipitation and coagulation of Fe, Cr(III), Al, and other hydroxides, forming dense, easily filterable flocs. S7 transports the slurry in reactor 3 to a plate and frame filter press via a screw pump for filtration. The filtration pressure is set to 4-6 bar. The filter cake is washed 1-3 times with deionized water. The washing water volume is 0.5-0.8 times the filter cake volume. After washing, the filtrate is collected in a refining mother liquor tank. The filter cake is automatically unloaded and stored in a centralized manner for recycling or harmless treatment as nickel-containing filter residue. S8 pumps the filtrate from the refined mother liquor tank into an activated carbon adsorption tank equipped with a stirrer, adds granular activated carbon to the adsorption tank, and stirs and adsorbs at 50-70 rpm at 20-30°C for 60-80 minutes; after adsorption, the activated carbon is separated through a 4-6 μm bag filter and further finely filtered through a 0.45-0.55 μm security filter. S9 passes the finely filtered mother liquor through a strongly acidic cation exchange resin bed. When the resin reaches saturation, the feed is stopped, and countercurrent regeneration is performed using 0.5~0.6 mol / L dilute sulfuric acid. After regeneration, the waste acid liquid rich in impurities is collected for subsequent separation and recovery or harmless treatment. The resin bed is backwashed with deionized water until neutral. S10 feeds the mother liquor after ion exchange treatment into a multi-effect falling film vacuum evaporator for concentration. The evaporation temperature is controlled at 83~87℃, and the vacuum degree is maintained at -0.08~-0.06 MPa. Concentration continues until the Ni concentration in the mother liquor is 235~245 g / L. After concentration, the mother liquor is cooled to 70~72℃, and a stirrer is started for homogenization. NiSO4·6H2O seed crystals are added to the homogenized concentrated mother liquor at a rate of 1~1.5% of the mother liquor mass. The mixture is stirred continuously at a speed of 30~50 rpm and cooled to 24~26℃. After cooling, the mixture is kept at 24~26℃ for 24~36 hours to promote full crystal growth and maturation. S11 The crystallized slurry is fed into a horizontal screw discharge centrifuge for solid-liquid separation. The centrifugation speed is set to 3500~4000 rpm and the centrifugation time is 5~10 minutes. The separated crystals are washed with deionized water at 5~10 ℃ for 1~3 times, and the washing water volume is 0.2~0.4 times the volume of the centrifuged crystals. The washed crystals are transferred to a double cone rotary vacuum dryer and dried at 58~62 ℃ and a vacuum degree of -0.08~-0.06 MPa until the moisture content of the crystals is 0.1~2.0%. The dried NiSO4·6H2O crystals are sealed in composite moisture-proof bags and stored in a dry and cool special warehouse. S12 sends the sodium sulfate-rich waste liquid generated during the filtration and washing process to a multi-effect evaporation crystallization system, where industrial-grade anhydrous sodium sulfate is recovered through evaporation, concentration, and cooling crystallization. The mother liquor after crystallization is treated and recycled. All nickel-containing filter residues are collected and leached with dilute sulfuric acid to recover nickel. The leaching solution is returned to the dissolution section for further treatment. The residues after leaching are rendered harmless and then disposed of in accordance with hazardous waste management regulations. All acid mist and exhaust gases from the production process are treated in series by a packed alkaline scrubbing tower and an activated carbon adsorber to ensure that emissions comply with national air pollutant emission standards.
[0009] According to a method for preparing battery-grade nickel sulfate by co-purification of crude nickel sulfate and crude nickel carbonate, the process water mentioned in S1 refers to water recovered from the solid-liquid separation step of this process or previous batches, which meets the reuse standards after treatment and quality testing, pre-treated industrial production water, and municipal tap water, or one or more combinations thereof.
[0010] Compared with the prior art, the present invention has the following advantages: (1) High-efficiency raw material utilization and cost saving: This invention creatively adopts a synergistic purification strategy of crude nickel sulfate and crude nickel carbonate. By precisely controlling the feeding ratio of crude nickel sulfate and crude nickel carbonate, and using crude nickel carbonate as an alkali source for batch neutralization, it effectively replaces part of the consumption of purchased soda ash, significantly reducing raw material costs and reagent expenses. At the same time, this synergistic effect optimizes the dissolution of nickel and the initial precipitation of impurities, improving the overall nickel recovery rate.
[0011] (2) Excellent multi-impurity removal efficiency: This invention constructs a multi-stage, refined impurity removal system. First, iron and aluminum are efficiently removed through Fe oxidation and preliminary precipitation. In particular, before the subsequent high-pH precipitation in the final stage, a sodium sulfite reduction step for hexavalent chromium (Cr(VI)) is introduced to completely convert it into easily precipitated trivalent chromium (Cr(III)). Combined with precipitation at pH 5.0~5.1, this ensures the complete removal of impurities such as chromium, residual iron, and aluminum, solving the problem of difficult Cr(VI) handling in traditional processes. The entire process ensures the specificity and efficiency of impurity removal through precise pH and ORP control.
[0012] (3) Product purity reaches ultra-high battery-grade standards: Based on chemical precipitation for impurity removal, this invention further introduces a deep purification process involving activated carbon adsorption and strong acidic cation exchange resin. Activated carbon effectively adsorbs trace organic matter in the solution, while ion exchange resin can precisely remove extremely low concentrations of metallic impurities (such as residual Cu, Ca, Mg, etc.), ensuring that the final nickel sulfate product meets the stringent battery-grade requirements for impurities such as Fe, Cr, and Cu (e.g., Fe≤10 ppm, Cr≤1 ppm, Cu≤10 ppm), providing a reliable guarantee for the production of high-quality lithium-ion battery cathode materials.
[0013] (4) Significant Environmental Friendliness and Resource Recycling: This invention highly values the concept of green production and achieves the recycling of multiple resources. The nickel-containing filtrate generated from filtration and washing is sent to the upstream process water pool for reuse, greatly reducing the consumption of fresh water. The sodium sulfate-rich waste liquid generated from the final stage of filtration is recycled to recover industrial-grade anhydrous sodium sulfate through evaporation and crystallization, turning waste into treasure. All nickel-containing filter residues are acid-leached to recover nickel, avoiding the waste of nickel resources. In addition, the synergistic neutralization and waste gas treatment system (alkali washing tower and activated carbon adsorption) ensures that gases such as acid mist and CO2 are emitted in compliance with standards, significantly reducing environmental pollution and waste disposal costs.
[0014] (5) Stable process and high operability: This invention sets clear and optimized control ranges for key parameters such as temperature, pH, ORP, stirring speed, feeding rate and time for each critical step (e.g., dissolution, neutralization, oxidation, reduction, precipitation, concentration and crystallization), resulting in good stability and repeatability of the entire process. This not only facilitates industrial-scale production and automated control, but also reduces operational difficulty, minimizes human error, and improves production efficiency and product consistency. Detailed Implementation
[0015] Example 1
[0016] Crude nickel sulfate and nickel carbonate were weighed separately in a ratio of 1.5:1. The crude nickel carbonate was crushed to a particle size of 1 mm, and the crude nickel sulfate was sieved to 1 mm to remove obvious mud and sand. Process water was prepared and filtered through a 1 μm screen for later use. Process water was added to reactor 1, accounting for 30% of the reactor's volume. The crude nickel sulfate was added to reactor 1 all at once, and the stirrer was started and stirred at 60 rpm and 60°C for 60 minutes. The crude nickel carbonate was divided into 4 portions, and one portion was added to the reactor every 20 minutes, while maintaining a speed of 60 rpm and a temperature of 60°C. Sodium carbonate was added to adjust the pH of the solution to 2.1 and maintained for 20 minutes. The CO2 and acid mist generated during the synergistic neutralization were discharged through the top of the reactor into an alkaline washing tower. The alkaline washing tower was filled with sodium hydroxide solution and the solution was kept circulating to ensure that the pH of the gas outlet was stable at 8. The gas after alkaline washing was further purified by an activated carbon adsorber and finally discharged in compliance with standards. The diaphragm metering pump was turned on to pump the mother liquor in reactor 1 at a rate of 10 L / min. A constant flow rate of n is pumped into reactor 2, which is equipped with a frame stirrer and a jacketed cooling system. The temperature inside the reactor is controlled at 60℃, and the stirring speed is 40 rpm. A 20% sodium hypochlorite solution is divided into four equal portions and added to reactor 2 at 15-minute intervals using a peristaltic pump. During the entire addition process, the ORP value is ensured to eventually stabilize at 340mV and maintained at this state for 10 minutes. Stirring is continued for 30 minutes to ensure complete oxidation reaction. Subsequently, a 30% sodium carbonate solution is pumped in at a rate of 10 L / h to adjust the pH to 3.1. After the pH reaches the set value, stirring is continued and the temperature is maintained for 60 minutes to allow the generated Fe(III) hydroxide and Al(OH)3 precipitate to fully coagulate and form easily separable flocculent material. The slurry in reactor 2 is transported to a plate and frame filter press by a screw pump. The filtration pressure is set at 4 bar until the filter cake water yield stabilizes at 60%. The filter cake is then filtered using a 40-ton filter press. The filter cake is washed once with warm water at ℃, with each wash using 0.5 times the volume of the filter cake. The filtrate after washing is collected and sent to the upstream process water tank for reuse. The filter cake is automatically unloaded into a sealed hopper as a nickel-containing byproduct or for further recycling. The mother liquor after preliminary solid-liquid separation is pumped into reactor 3 at a flow rate of 10 L / min using a diaphragm pump. Reactor 3 is equipped with a paddle stirrer and a jacketed heating system. The temperature inside the reactor is controlled at 54℃, and the stirring speed is 40 rpm. A 30% sodium sulfite solution is divided into three equal portions and added to reactor 3 at 20-minute intervals. Stirring is maintained during the addition process, and the temperature is kept at 54℃. After the reducing agent is added, stirring continues and the temperature is maintained for 45 minutes to ensure that Cr(VI) is completely reduced to Cr(III) and the Cr(VI) concentration in the solution is below 0.1 mg / L. A 30% sodium carbonate solution is pumped into reactor 3 to adjust the pH of the system to 5.0; After the pH reaches the set value, continue stirring and keep warm for 80 minutes to promote the full precipitation and coagulation of hydroxides such as Fe, Cr(III), and Al, forming dense, easily filterable flocs; The slurry in reactor 3 is transported to a plate and frame filter press for filtration using a screw pump, with the filtration pressure set at 4 bar; The filter cake is washed once with deionized water, with the washing water volume being 0.5 times the filter cake volume. After washing, the filtrate is collected in a refining mother liquor tank, and the filter cake is automatically unloaded and centrally stored for recycling or harmless treatment as nickel-containing filter residue; The filtrate in the refining mother liquor tank is pumped into a pump equipped with a stirrer. The activated carbon adsorption tank was used. Granular activated carbon was added to the adsorption tank, and the mixture was stirred at 50 rpm at 20°C for 60 minutes for adsorption. After adsorption, the activated carbon was separated through a 4 μm bag filter and further finely filtered through a 0.45 μm security filter. The mother liquor after fine filtration was passed through a strongly acidic cation exchange resin bed. When the resin reached saturation, the feed was stopped, and the resin was regenerated countercurrently using 0.5 mol / L dilute sulfuric acid. After regeneration, the waste acid liquid rich in impurities was collected for subsequent separation and recovery or harmless treatment. The resin bed was backwashed with deionized water until it reached a medium concentration. The mother liquor, after ion exchange treatment, was concentrated in a multi-effect falling film vacuum evaporator at a temperature controlled at 83-87°C and a vacuum maintained at -0.08 MPa. Concentration continued until the Ni concentration in the mother liquor reached 235 g / L. After concentration, the mother liquor was cooled to 70°C, and a stirrer was started for homogenization. NiSO4·6H2O seed crystals were added to the homogenized concentrated mother liquor at 1% of the mother liquor mass, and the mixture was stirred continuously at 30 rpm while cooling to 24°C. After cooling, the mixture was kept at 24°C for 24 hours to promote crystal formation. The crystals were allowed to fully grow and mature. The matured slurry was then fed into a horizontal screw centrifuge for solid-liquid separation at 3500 rpm for 5 minutes. The separated crystals were washed once with deionized water at 5°C, with the water volume being 0.2 times the volume of the centrifuged crystals. The washed crystals were then transferred to a double-cone rotary vacuum dryer and dried at 58°C and a vacuum of -0.08 MPa until the moisture content was 0.1%. The dried NiSO4·6H2O crystals were then sealed in composite moisture-proof bags and stored in a dry, cool, and specialized warehouse. Example 2
[0017] Crude nickel sulfate and nickel carbonate were weighed separately in a ratio of 1.8:1. The crude nickel carbonate was crushed to a particle size of 2 mm, and the crude nickel sulfate was sieved to 3 mm to remove obvious mud and sand. Process water was prepared and filtered through a 3 μm screen for later use. Process water was added to reactor 1, accounting for 35% of the reactor's volume. The crude nickel sulfate was added to reactor 1 all at once, and the stirrer was started and stirred at 70 rpm and 65°C for 70 minutes. The crude nickel carbonate was divided into 4 portions, and one portion was added to the reactor every 25 minutes, while maintaining a speed of 70 rpm and a temperature of 65°C. Sodium carbonate was added to adjust the pH of the solution to 2.2 and maintained for 25 minutes. The CO2 and acid mist generated during the synergistic neutralization were discharged through the top of the reactor into an alkaline washing tower. The alkaline washing tower was filled with sodium hydroxide solution and the solution was kept circulating to ensure that the pH of the gas outlet was stable at 8. The gas after alkaline washing was further purified by an activated carbon adsorber and finally discharged in compliance with standards. The diaphragm metering pump was turned on to pump the mother liquor in reactor 1 at a rate of 15... A constant flow rate of L / min was pumped into reactor 2, which was equipped with a frame stirrer and a jacketed cooling system. The temperature inside the reactor was controlled at 63℃, and the stirring was performed at 50 rpm. A 22% sodium hypochlorite solution was added to reactor 2 in four equal portions via a peristaltic pump, with each portion added at 18-minute intervals. Throughout the addition process, the ORP value was ensured to stabilize at 345 mV and maintained at this level for 15 minutes, followed by stirring for 45 minutes to ensure complete oxidation. Subsequently, a 31% sodium carbonate solution was pumped in at a rate of 15 L / h to adjust the pH to 3.2. After the pH reached the set value, stirring and heat preservation were continued for 70 minutes to allow the generated Fe(III) hydroxide and Al(OH)3 precipitate to fully coagulate, forming easily separable flocs. The slurry in reactor 2 was then pumped to a plate and frame filter press via a screw pump, with the filtration pressure set at 5 bar until the filter cake effluent rate stabilized at 70%. The filter cake was then subjected to 45... The filter cake was washed twice with warm water at ℃, with each wash using 0.6 times the volume of the filter cake. The filtrate was collected and sent to the upstream process water tank for reuse. The filter cake was automatically unloaded into a sealed hopper as a nickel-containing byproduct or for further recycling. The mother liquor after preliminary solid-liquid separation was pumped into reactor 3 at a flow rate of 15 L / min using a diaphragm pump. Reactor 3 was equipped with a paddle stirrer and a jacketed heating system. The temperature inside the reactor was controlled at 55℃, and the stirring was performed at a speed of 50 rpm. A 31% sodium sulfite solution was divided into three equal portions and added to reactor 3 at 25-minute intervals. Stirring was maintained during the addition process, and the temperature was kept at 55℃. After the reducing agent was added, stirring continued and the temperature was maintained for 50 minutes to ensure that Cr(VI) was completely reduced to Cr(III) and the Cr(VI) concentration in the solution was below 0.1 mg / L. A 31% sodium carbonate solution was pumped into reactor 3 to adjust the pH of the system to 5.0; After the pH reaches the set value, continue stirring and keep warm for 85 minutes to promote the full precipitation and coagulation of hydroxides such as Fe, Cr(III), and Al, forming dense, easily filterable flocs; The slurry in reactor 3 is transported to a plate and frame filter press for filtration using a screw pump, with the filtration pressure set at 5 bar; The filter cake is washed twice with deionized water, with the washing water volume being 0.6 times the filter cake volume. After washing, the filtrate is collected in a refining mother liquor tank, and the filter cake is automatically unloaded and centrally stored for recycling or harmless treatment as nickel-containing filter residue; The filtrate in the refining mother liquor tank is pumped into an activated carbon adsorption tank equipped with a stirrer, and granular activated carbon is added to the adsorption tank. The tank is stirred and adsorbed at 60 rpm at 25°C for 70 minutes; After adsorption, the activated carbon is separated through a 5 μm bag filter and further finely filtered through a 0.5 μm security filter; The finely filtered mother liquor is passed through a strongly acidic cation exchange resin bed. When the resin reaches saturation, the feed is stopped, and 0.55 The resin bed was regenerated countercurrently using dilute sulfuric acid at mol / L. After regeneration, the impurity-rich waste acid was collected for subsequent separation, recovery, or harmless treatment. The resin bed was backwashed with deionized water until neutral. The mother liquor after ion exchange treatment was sent to a multi-effect falling film vacuum evaporator for concentration, with the evaporation temperature controlled at 85℃ and the vacuum maintained at -0.07MPa. Concentration continued until the Ni concentration in the mother liquor reached 240 g / L. After concentration, the mother liquor was cooled to 71℃, and a stirrer was started for homogenization. NiSO4·6H2O seed crystals were added to the homogenized concentrated mother liquor at a concentration of 40 mol / L. The amount added was 1.2% of the mother liquor mass. The mixture was continuously stirred at rpm and cooled to 25℃. After cooling, it was kept still at 25℃ for 30 hours to promote full crystal growth and maturation. The matured slurry was then fed into a horizontal screw discharge centrifuge for solid-liquid separation at 3800 rpm for 7 minutes. The separated crystals were washed twice with deionized water at 7℃, with the water volume being 0.3 times the volume of the centrifuged crystals. The washed crystals were then transferred to a double-cone rotary vacuum dryer and dried at 60℃ and a vacuum of -0.07 MPa until the moisture content of the crystals was 1.0%. The dried NiSO4·6H2O crystals were then sealed in composite moisture-proof bags and stored in a dry, cool, and dedicated warehouse. Example 3
[0018] Crude nickel sulfate and nickel carbonate were weighed separately in a ratio of 2:1. The crude nickel carbonate was crushed to a particle size of 3 mm, and the crude nickel sulfate was sieved to 5 mm to remove obvious mud and sand. Process water was prepared and filtered through a 5 μm screen for later use. Process water was added to reactor 1, accounting for 40% of the reactor's volume. The crude nickel sulfate was added to reactor 1 all at once, and the stirrer was started and stirred at 80 rpm and 70°C for 80 minutes. The crude nickel carbonate was divided into 5 portions, and one portion was added to the reactor every 30 minutes, while maintaining a speed of 80 rpm and a temperature of 70°C. Sodium carbonate was added to adjust the pH of the solution to 2.3 and maintained for 30 minutes. The CO2 and acid mist generated during the synergistic neutralization were discharged through the top of the reactor into an alkaline washing tower. The alkaline washing tower was filled with sodium hydroxide solution and the solution was kept circulating to ensure that the pH of the gas outlet was stable at 9. The gas after alkaline washing was further purified by an activated carbon adsorber and finally discharged in compliance with standards. The diaphragm metering pump was turned on to pump the mother liquor in reactor 1 at a rate of 20... A constant flow rate of L / min is pumped into reactor 2, which is equipped with a frame stirrer and a jacketed cooling system. The temperature inside the reactor is controlled at 65℃, and the stirring speed is 60 rpm. A 20-25% sodium hypochlorite solution is added to reactor 2 in five equal portions via a peristaltic pump at 20-minute intervals. Throughout the addition process, the ORP value is kept stable at 350 mV for 20 minutes, followed by stirring for 60 minutes to ensure complete oxidation. Subsequently, a 32% sodium carbonate solution is pumped in at a rate of 20 L / h to adjust the pH to 3.3. After the pH reaches the set value, stirring and heat preservation continue for 80 minutes to allow the generated Fe(III) hydroxide and Al(OH)3 precipitate to fully coagulate and form easily separable flocs. The slurry in reactor 2 is then pumped to a plate and frame filter press via a screw pump. The filtration pressure is set to 6 bar until the filter cake effluent rate stabilizes at 75%. The filter cake is then treated with 50... The filter cake was washed three times with warm water at ℃, with each wash using 0.8 times the volume of the filter cake. The filtrate was collected and sent to the upstream process water tank for reuse. The filter cake was automatically unloaded into a sealed hopper as a nickel-containing byproduct or for further recycling. The mother liquor after preliminary solid-liquid separation was pumped into reactor 3 at a flow rate of 20 L / min using a diaphragm pump. Reactor 3 was equipped with a paddle stirrer and a jacketed heating system. The temperature inside the reactor was controlled at 56℃, and the stirring speed was 60 rpm. A 32% sodium sulfite solution was divided into four equal portions and added to reactor 3 at 30-minute intervals. Stirring was maintained during the addition process, and the temperature was kept at 56℃. After the reducing agent was added, stirring continued and the temperature was maintained for 60 minutes to ensure that Cr(VI) was completely reduced to Cr(III) and the Cr(VI) concentration in the solution was below 0.1 mg / L. A 32% sodium carbonate solution was pumped into reactor 3 to adjust the pH of the system to 5.1. After the pH reaches the set value, continue stirring and keep warm for 90 minutes to promote the full precipitation and coagulation of hydroxides such as Fe, Cr(III), and Al, forming dense, easily filterable flocs. The slurry in reactor 3 is then pumped to a plate and frame filter press for filtration at a pressure of 6 bar. The filter cake is washed three times with deionized water, with a washing volume of 0.8 times the filter cake volume. After washing, the filtrate is collected in a refining mother liquor tank. The filter cake is automatically unloaded and stored centrally for recycling or harmless treatment as nickel-containing filter residue. The filtrate in the refining mother liquor tank is pumped into an activated carbon adsorption tank equipped with a stirrer. Granular activated carbon is added to the adsorption tank, and the mixture is stirred at 70 rpm at 30°C and adsorbed for 80 minutes. After adsorption, the activated carbon is separated through a 6 μm bag filter and further finely filtered through a 0.55 μm security filter. The finely filtered mother liquor is then passed through a strongly acidic cation exchange resin bed. Feeding is stopped when the resin reaches saturation, and 0.6... The resin bed was regenerated countercurrently with dilute sulfuric acid at mol / L. After regeneration, the waste acid solution rich in impurities was collected for subsequent separation, recovery, or harmless treatment. The resin bed was backwashed with deionized water until neutral. The mother liquor after ion exchange treatment was sent to a multi-effect falling film vacuum evaporator for concentration, with the evaporation temperature controlled at 87℃ and the vacuum maintained at -0.06 MPa. Concentration was continued until the Ni concentration in the mother liquor was 245 g / L. After concentration, the mother liquor was cooled to 72℃ and the stirrer was started for homogenization. NiSO4·6H2O seed crystals were added to the homogenized concentrated mother liquor at a rate of 1.5% of the mother liquor mass. The mixture was stirred continuously at 50 rpm and cooled to 26℃. After cooling, the mixture was kept still at 26℃ for 36 hours to promote full crystal growth and maturation. The matured slurry was sent to a horizontal screw discharge centrifuge for solid-liquid separation. The centrifugation speed was set to 4000 rpm and the centrifugation time was 10 minutes. The separated crystals were then subjected to 10... The crystals were washed three times with deionized water at ℃, with the washing water volume being 0.4 times the volume of the centrifuged crystals. After washing, the crystals were transferred to a double-cone rotary vacuum dryer and dried at 62℃ and a vacuum of -0.06 MPa until the moisture content of the crystals was 2.0%. The dried NiSO4·6H2O crystals were then sealed in composite moisture-proof bags and stored in a dry, cool, and dedicated warehouse. Example 4
[0019] To verify the purity of the battery-grade nickel sulfate prepared by this invention, rigorous purity testing was conducted on the NiSO4·6H2O crystal products obtained in Examples 1 to 3. The testing items mainly included nickel content and the content of various key impurity elements to comprehensively assess whether the products met the various requirements for battery-grade nickel sulfate. Before purity testing, all samples were sampled and pretreated according to standard operating procedures. Representative samples were randomly selected from the dried NiSO4·6H2O crystals prepared in each example, ground into a fine powder, and a certain amount was accurately weighed and dissolved in ultrapure water to prepare the test solution.
[0020] In the testing process, nickel content is determined using disodium ethylenediaminetetraacetate (EDTA) complexometric titration. The test solution is titrated to the endpoint with standard EDTA solution to accurately calculate the nickel content. For impurity element content, inductively coupled plasma optical emission spectrometry (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS) is used for simultaneous multi-element analysis to ensure accuracy and extremely high sensitivity to trace impurities. Before analysis, a series of standard curves are prepared using high-purity standard solutions. The prepared sample solution is then introduced into the instrument for measurement, and the actual content of key metallic impurities such as iron, chromium, copper, aluminum, calcium, magnesium, zinc, manganese, and cobalt in the crystalline product is calculated based on the standard curves. Furthermore, the moisture content of the product is accurately determined using the Karl Fischer coulometric method.
[0021] Following the rigorous testing procedures outlined above, the purity test data for the battery-grade nickel sulfate products prepared in Examples 1, 2, and 3 are as follows. Referring to the battery-grade nickel sulfate standard, the nickel content (Ni) is required to be no less than 22.1%. Actual test results show that the nickel content in Example 1 reached 22.3%, in Example 2 it was 22.25%, and in Example 3 it was 22.2%, all significantly exceeding the standard requirements.
[0022] Regarding impurity control, the standard for battery-grade nickel sulfate requires an iron (Fe) content of less than 10 ppm. In Example 1 of this invention, the iron content was 3 ppm, in Example 2 it was 5 ppm, and in Example 3 it was 4 ppm, all far below the standard limit. For chromium (Cr), the standard requires less than 1 ppm, while the detection results of all three examples were less than 0.1 ppm, reaching the instrument's detection limit, indicating that chromium impurities were effectively removed. The standard limit for copper (Cu) is 10 ppm. The copper content in Examples 1 and 3 was 2 ppm, and in Example 2 it was 3 ppm, also far below the standard. The standard requirement for aluminum (Al) is less than 5 ppm. The aluminum content in Examples 1 and 3 was 1 ppm, and in Example 2 it was 2 ppm. The standard limits for calcium (Ca) and magnesium (Mg) are both 10 ppm. In Example 1, the calcium content was 3 ppm and the magnesium content was 4 ppm; in Example 2, the calcium content was 4 ppm and the magnesium content was 5 ppm; and in Example 3, the calcium content was 3 ppm and the magnesium content was 4 ppm. These values all meet or exceed the standard. As for zinc (Zn) and manganese (Mn), the standard requires levels below 5 ppm, while the detection values in all three examples were below 0.5 ppm, indicating that these impurities were completely removed. The standard limit for cobalt (Co) is 50 ppm, and the cobalt contents in Examples 1, 2, and 3 were 15 ppm, 20 ppm, and 18 ppm, respectively, which are also far below the standard requirements.
[0023] Finally, regarding moisture content, the standard for battery-grade nickel sulfate requires a moisture content of less than 2.0%. The three embodiments of the present invention were measured to have moisture contents of 0.1%, 1.0%, and 2.0%, respectively, all of which meet the stringent requirements for battery-grade products.
[0024] The test data clearly show that the nickel sulfate products prepared in Examples 1, 2, and 3 all meet or exceed the standard requirements for nickel content. Simultaneously, the contents of key impurity elements (such as Fe, Cr, Cu, Al, Ca, Mg, Zn, Mn, and Co) are far below the control standards for battery-grade nickel sulfate. In particular, the content of heavy metal impurities such as chromium is below the detection limit. The moisture content of the products also fully meets the requirements for battery-grade products. These results fully demonstrate that the proposed method for the synergistic purification of crude nickel sulfate and crude nickel carbonate can stably and efficiently prepare nickel sulfate products that meet the high purity requirements for battery-grade products.
[0025] Please note to all technical personnel: Although the present invention has been described according to the specific embodiments above, the inventive concept of the present invention is not limited to this invention. Any modifications that utilize the inventive concept will be included within the scope of protection of this patent.
Claims
1. A method for preparing battery grade nickel sulfate by co-purification of crude nickel sulfate and crude nickel carbonate, characterized in that, The method for preparing battery-grade nickel sulfate by synergistically purifying the crude nickel sulfate and the crude nickel carbonate comprises the following steps: S1: crude nickel sulfate and nickel carbonate are weighed respectively, and the ratio of the two is 1.5-2:1; the crude nickel carbonate is crushed to a particle size of 1-3 mm, and the crude nickel sulfate is sieved to 1-5 mm and the obvious mud sand is removed; process water is prepared and filtered through a filter screen of 1-5 μm for standby; S2: process water is added to the reaction kettle 1, and the process water accounts for 30-40% of the reaction kettle 1; the crude nickel sulfate is added to the reaction kettle 1 at one time, the stirrer is started to stir at a speed of 60-80 rpm and a temperature of 60-70℃ for 60-80 minutes; the crude nickel carbonate is divided into 4-5 parts, and one part of the crude nickel carbonate is added to the reaction kettle every 20-30 minutes, while the speed of 60-80 rpm and the temperature of 60-70℃ are maintained; sodium carbonate is added to adjust the pH of the solution to 2.1-2.3, and the solution is maintained for 20-30 minutes; S3: the CO2 and acid mist generated during the synergistic neutralization are led out through the top of the kettle and enter the alkali washing tower, the alkali washing tower is filled with sodium hydroxide solution and the solution is circulated to ensure that the pH of the gas outlet is stable at 8-9; the gas after alkali washing is further purified by an activated carbon adsorber, and finally meets the emission standard; S4: the diaphragm metering pump is started, and the mother liquor in the reaction kettle 1 is pumped into the reaction kettle 2 at a constant flow rate of 10-20 L / min, the reaction kettle 2 is equipped with a frame stirrer and a jacket cooling system, the temperature in the kettle is controlled at 60-65℃ and the stirring speed is 40-60 rpm; 20-25% of sodium hypochlorite solution is divided into 4-5 equal parts and added to the reaction kettle 2 every 15-20 minutes; During the whole adding process, the ORP value is finally stabilized at 340-350 mV, and this state is maintained for 10-20 minutes, and the stirring is continued for 30-60 minutes to ensure that the oxidation reaction is complete; then 30-32% of sodium carbonate solution is pumped in at a rate of 10-20 L / h to adjust the pH to 3.1-3.3; after the pH reaches the set value, continue to stir and keep warm for 60-80 minutes to make the generated Fe(III) hydroxide and Al(OH)3 precipitate fully coagulate to form flocculent material which is easy to separate; S5: the slurry in the reaction kettle 2 is transported to the plate and frame filter press by a screw pump, the filter pressing pressure is set to 4-6 bar, and the filter cake is washed with warm water at 40-50℃ for 1-3 times, and the water amount for each washing is 0.5-0.8 times the volume of the filter cake; the filtrate after washing is collected and sent to the front-end process water pool for reuse; the filter cake is automatically unloaded to a sealed hopper as a nickel-containing byproduct or further recovered and processed; S6The mother liquor after the initial solid-liquid separation is pumped into the reaction kettle 3 at a flow rate of 10-20 L / min by a diaphragm pump. The reaction kettle 3 is equipped with a paddle stirrer and a jacket heating system, and the temperature in the kettle is controlled at 54-56℃ and stirred at a speed of 40-60 rpm. 30-32% sodium sulfite solution is added to the reaction kettle 3 in 3-4 equal portions at an interval of 20-30 minutes each. During the addition process, stirring is maintained and the temperature is maintained at 54-56℃. After the addition of the reducing agent is completed, continue to stir and keep warm for 45-60 minutes to ensure that Cr(VI) is completely reduced to Cr(III) and the concentration of Cr(VI) in the solution is less than 0.1 mg / L. Pump 30-32% sodium carbonate solution into the reaction kettle 3 to adjust the pH of the system to 5.0-5.
1. After the pH reaches the set value, continue to stir and keep warm for 80-90 minutes to promote the precipitation and coagulation of Fe, Cr(III), Al and other hydroxides, forming a dense and easy-to-filter flocculation; S7The slurry in the reaction kettle 3 is transported to a plate and frame filter press by a screw pump for pressure filtration, and the pressure filtration pressure is set to 4-6 bar. The filter cake is washed with deionized water for 1-3 times, and the washing water amount is 0.5-0.8 times the volume of the filter cake. After washing, the filtrate is collected in a refined mother liquor tank, the filter cake is automatically unloaded and stored for recovery or harmless treatment as a nickel-containing residue; S8The filtrate in the refined mother liquor tank is pumped into an activated carbon adsorption tank equipped with a stirrer, and granular activated carbon is added to the adsorption tank. Stirring and adsorption are carried out at 20-30℃ and a stirring speed of 50-70 rpm for 60-80 minutes. After adsorption is completed, the activated carbon is separated by a bag filter with a pore size of 4-6 μm, and further refined by a security filter with a pore size of 0.45-0.55 μm; S9The refined mother liquor is passed through a strong acid cation exchange resin bed. When the resin reaches saturation, the feeding is stopped and 0.5-0.6 mol / L dilute sulfuric acid is used for countercurrent regeneration. After regeneration, the regenerated waste acid liquid rich in impurities is collected for subsequent separation and recovery or harmless treatment, and the resin bed is backwashed to neutral with deionized water; S10The mother liquor after ion exchange treatment is sent to a multi-effect falling film vacuum evaporator for concentration. The evaporation temperature is controlled at 83-87℃, and the vacuum degree is maintained at -0.08~-0.06 MPa. Continuous concentration is carried out until the Ni concentration in the mother liquor is 235-245 g / L. After concentration is completed, the mother liquor is cooled to 70-72℃, and the stirrer is started for homogenization. To the homogenized concentrated mother liquor, add NiSO4·6H2O seed crystals in an amount of 1-1.5% of the mass of the mother liquor, and continuously stir at a speed of 30-50 rpm and cool to 24-26℃. After cooling is completed, keep still at 24-26℃ for 24-36 hours to promote the growth and maturity of the crystals; S11 send the slurry of crystalline maturity into horizontal screw discharge centrifuge for solid-liquid separation, the centrifugal speed is set to 3500~4000 rpm, the centrifugal time is 5~10 minutes; the separated crystal is washed with 5~10 ℃ deionized water for 1~3 times, the washing water volume is 0.2~0.4 times of the centrifugal crystal volume; the washed crystal is transferred into double-cone rotary vacuum drying machine, dried at 58~62 ℃, the vacuum degree is-0.08~-0.06 MPa, until the crystal moisture content is 0.1~2.0%; the dried NiSO4·6H2O crystal is sealed and packaged in a composite moisture-proof bag, stored in a dry and cool special warehouse; S12 send the waste liquid rich in sodium sulfate generated in the process of pressure filtration and washing into a multi-effect evaporation crystallization system, recover industrial-grade anhydrous sodium sulfate by evaporation concentration and cooling crystallization; The mother liquor after crystallization is recycled after treatment, all the nickel-containing filter residues are collected, nickel is recovered by dilute sulfuric acid leaching, and the leaching solution is returned to the dissolution section for treatment; the leached residue is harmless treated, and finally disposed according to the hazardous waste management standard; all the acid mist and waste gas in the production process are treated by a series connection of a packed alkali washing tower and an activated carbon adsorber, to ensure that the emission meets the national atmospheric pollutant emission standard.
2. The method for preparing battery-grade nickel sulfate by co-purification of crude nickel sulfate and crude nickel carbonate as described in claim 1, characterized in that, The process water in S1 refers to one or more of the following: water recovered from the solid-liquid separation step of the process or previous batches, treated and quality tested to meet the recycling standards, pretreated industrial water, and municipal tap water.
Citation Information
Cited By
Continuous crystallization process of high-purity nickel nitrate hexahydrate
CN122144798A
